Association Between Polypharmacy and Frailty in Elderly Patients Receiving Care at a Public Hospital in South India - Vishwas, Hunsur Nagendra; Tulasedas, Shalini; Sivakumar, Mohana Vishnu Varadhan; Ayyanar, Gurulakshmi; Nagarajan, Naveena; Sivasubramaniam, Balaji; S, Arthi; Ponnusankar, Sivasankaran (Biomedical Sciences and Clinical Medicine, 2026)
Objective This study analyses the impact of polypharmacy on frailty among the elderly patients visiting the public sector hospitals. The present study was done to assess the frailty status of the elderly patients and to see whether the individuals with polypharmacy exhibited more frailty when compared to those without polypharmacy. Methods This is a case-control study that included 488 participants age 60 years and above who visited the general medicine department of Public Hospital Ooty, India. Polypharmacy was defined as the concomitant use of 5 or more medications. Frailty status of the participants was assessed using the Tilburg Frailty Indicator. Results Polypharmacy was found to be present in 34.42% of cases. The prevalence of frailty was significantly higher in the polypharmacy group, affecting 41.07% of the study participants. Finally, three variables emerged as influential predictors of polypharmacy namely, 3 or more diseases (AOR 6.303, Cl 4.009-9.911, p < 0.0001), unsatisfied sleep status (AOR 1.669, Cl 1.068-2.606, p = 0.01), and people taking frailty causing drugs (AOR 4.328, Cl 2.628-7.128, p = 0.003). Additionally, there was a moderate relationship between modified lifestyle (smoking, alcohol consumption) and polypharmacy. Conclusions The results suggest that polypharmacy is linked with frailty among the elderly population, highlighting the importance of clinician awareness of these factors.